2023
DOI: 10.1007/s10533-023-01031-0
|View full text |Cite
|
Sign up to set email alerts
|

Surprising relationships between soil pH and microbial biomass and activity in a northern hardwood forest

Abstract: Soil microbes mediate major biogeochemical processes in forest ecosystems. Soil pH is considered a "master variable" controlling these processes and many biogeochemical processes in turn in uence pH. Long-term measurements of soil pH, microbial biomass carbon (C) and nitrogen (N) content, microbial respiration, potential net N mineralization and nitri cation rates, denitri cation potential, and soil nitrate (NO 3 -) and ammonium (NH + 4 ) concentrations have occurred since 1994 at the Hubbard Brook Experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We found the same pattern in total and dissolved soil contents, which were also highest at Dav. This indicates for the mineral topsoil that microbial C, N, and S are positively related to soil content but negatively to pH, as shown in recent studies [27,53]. As the MBS contents are considered to be the most active S pool in S-turnover in soil, higher MBS contents indicate a greater S availability for higher plants [26].…”
Section: Ph Effects On Microbial Mineralizationmentioning
confidence: 65%
See 1 more Smart Citation
“…We found the same pattern in total and dissolved soil contents, which were also highest at Dav. This indicates for the mineral topsoil that microbial C, N, and S are positively related to soil content but negatively to pH, as shown in recent studies [27,53]. As the MBS contents are considered to be the most active S pool in S-turnover in soil, higher MBS contents indicate a greater S availability for higher plants [26].…”
Section: Ph Effects On Microbial Mineralizationmentioning
confidence: 65%
“…However, unexpected effects of pH changes on microbial biomass and activity in forest soils were also observed in northern hardwood forest plots, and underlying microbial processes are not completely understood [53]. Liming of acidified soils during recovery from pollution has a strong influence on the pH-dependence of microbial activity and therefore crucially impacts S mineralization processes.…”
Section: Ph Effects On Microbial Mineralizationmentioning
confidence: 99%
“…In agreement with this, the random forest result showed that among multiple factors, soil N‐cycling traits (e.g., TN, BA, MBN, and denitrifying genes) significantly explained soil δ 15 N changes in wetter sites, which provides robust evidence that 15 N enrichment under relative drought conditions may largely result from strong soil N losses through microbe‐driven N transformations under high N availability conditions. Additionally, this microbe‐driven mechanism of soil 15 N enrichment is further supported by the pronounced contribution of soil pH to soil δ 15 N. As a key factor shaping microbial structure and function, soil pH strongly affects soil N‐cycling microbial communities (Ontman et al., 2023; Rousk et al., 2010; Scarlett et al., 2021). Our results showed that pH was the most pronounced driver of soil δ 15 N in wetter sites, with dramatically different pH values under different aridity conditions (Figure S5), indirectly highlighting the contribution of microbe‐driven N cycling to soil δ 15 N. Overall, these findings show that in wetter regions, soil 15 N closely tracked with soil N dynamics, suggesting that soil 15 N isotopes can accurately reflect soil N cycling and N availability in low aridity environments (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the random forest result showed that among multiple factors, soil N-cycling traits (e.g., TN, BA, MBN, and denitrifying genes) significantly explained soil δ 15 N changes in wetter sites, which provides robust evidence that 15 N enrichment under relative drought conditions may largely result from strong soil N losses through microbe-driven N transformations under high N availability conditions. Additionally, this microbe-driven mechanism of soil 15 N enrichment is further supported by the pronounced contribution of soil pH to soil δ 15 N. As a key factor shaping microbial structure and function, soil pH strongly affects soil N-cycling microbial communities (Ontman et al, 2023;Rousk et al, 2010;Scarlett et al, 2021). Our with increasing aridity.…”
Section: Soil δ 15 N Patterns Along the Aridity Gradientmentioning
confidence: 90%
“…The practice of burning plant residues and the use of mineral fertilizers may have contributed to the increase in soil acidity over time, as these practices reduce soil pH and favor the release of hydrogen ions (H+) and aluminum (Al + 3) (Chaves et al 2020). This continuous acidi cation process may be intensi ed due to base losses by leaching, dissolution reactions of CO 2 in the soil solution, dissociation of H + ions from organic and inorganic radicals by microbial activity(Ontman et al 2023).…”
mentioning
confidence: 99%